Associations of Chronotype, Daily Intake of Fat, Fiber, Magnesium, and Potassium with Blood Pressure among Adolescents - M Berri Ridhoka; Dono Indarto; Muthmainah Muthmainah (Universitas Aisyah Pringsewu, 2023)
Circadian rhythm and daily intake of fat, fiber, and micronutrients have a different relationship to blood pressure. This study analyzed the relationship of chronotype, daily intake of fat, fiber, magnesium, and potassium with blood pressure in adolescents. One hundred and forty-three students from several schools in Kerinci Regency, Jambi Province participated in this cross-sectional study. Chronotype data and daily intake were obtained using a questionnaire. Chronotype was analyzed using chi-square while daily intake of fat, fiber, magnesium, and potassium were analyzed using rank spearman. The relationship variables were further analyzed using multiple linear regression. A total of 34.4% of adolescents were found to have stage 1 and 2 hypertension. In bivariate analyzed, chronotype was significantly related to systolic (p= 0.001 OR=3.68) and diastolic blood pressure (p=0.01 OR=3.03), while daily intake of fat was significantly related only to systolic blood pressure (p= 0.000 r=0.306). daily intake of fiber, magnesium, and potassium were not related to blood pressure. In multivariate analyzed, chronotype (p= 0,015 B= 5,53), daily intake of fat (p= 0,00 B= 0,31), and fiber (p= 0,041 B= -0,66) were significantly related to systolic blood. Daily intake of fat had the greatest influence on systolic blood pressure (Standardized Coefficient = 0.358). while on diastolic blood pressure, only chronotype (p= 0.013 B= 3,51) and daily intake of fat (p= 0,027 B= 0,1) were significantly related. Chronotype had the greatest influence on diastolic blood pressure (Standardized Coefficient = 0.211). Abstrak: Irama sirkadian dan kebiasaan asupan lemak, serat dan mikronutrien memiliki hubungan yang berbeda terhadap tekanan darah. Penelitian ini menganalisis hubungan chronotype, kebiasaan asupan lemak, serat, magnesium, dan kalium dengan tekanan darah remaja. Seratus empat puluh tiga siswa dari bebearapa sekolah di Kabupaten Kerinci, Provinsi Jambi berpartisipasi dalam penelitian cross-sectional ini. Data cronotype dan kebiasaan asupan didapat dengan menggunakan kuesioner. Chronotype dianalisis menggunakan uji chi square sementara kebiasaan asupan lemak, serat, magnesium dan kalium dianalisis menggunakan rank spearman. Hubungan antar variabel lebih jauh dianalisis menggunakan regresi linier berganda. Total 34,4% remaja mengalami hipertensi stage 1 dan 2. Pada analisis bivariat, chronotype berhubungan signifikan terhadap tekanan darah sistolik (p= 0.001 OR=3.68) dan diastolik (p=0.01 OR=3.03) sementara kebiasaan asupan lemak berhubungan signifikan hanya dengan tekanan darah sistolik (p= 0.000 r=0.306). Kebiasaan asupan serat, magnesium dan kalium tidak berhubungan dengan tekanan darah. Pada analisis multivariat, chronotype (p= 0,015 B= 5,53), kebiasaan asupan lemak (p= 0,00 B= 0,31), dan serat (p= 0,041 B= -0,66) berhubungan secara signifikan terhadap tekanan darah sistolik. Kebiasaan asupan lemak memiliki pengaruh terbesar terhadap tekanan darah sistolik (Standardized Coefficient = 0.358). Sementara pada tekanan darah diastolik, hanya chronotype (p= 0.013 B= 3,51) dan kebiasaan asupan lemak (p= 0,027 B= 0,1) yang berhubungan secara signifikan. Chronotype memiliki pengaruh terbesar terhadap tekanan darah diastolik (Standardized Coefficient = 0.211).